Adoption of Sustainable Land Management Practices Among Smallholder Farmers in Sekota District, North-eastern Ethiopia - Asresu, Melaku (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Despite the government and non-governmental organizations have promoted sustainable land management practices to improve agricultural productivity, however; the adoption rate of these practices among smallholder farmers remains low. This study aimed to analyze the determinant factors influencing the adoption of sustainable land management practices and identify the major challenges and constraints in adopting these practices. The data was collected from 267 households randomly using a multistage sampling technique, which included household survey, key informant interviews, and focus group discussions from three sample kebeles in Sekota district during in 2024 production season. Descriptive, inferential statistics and multinomial logit models were used for analyzing quantitative data while the qualitative data was analyzed by interpretation, narrations, and conceptual generalization. The multinomial regression result indicates that; the adoption of livestock manure was positively influenced by household age, education, livestock holdings, and income (P ≤ 10%), while the slope of farmlands and farm size negatively the adoption of livestock manure; compost adoption was positively linked to education, livestock holdings, credit access, and training (P ≤ 10%, whereas age, slope of farmlands and farm size negatively the adoption of compost. Inorganic fertilizer adoption was influenced by education, farm experience, credit access, and income (P ≤ 10%) age, distance to farmlands, slope of farmlands and farm size negatively the adoption of inorganic fertilizer. Integrated methods were positively affected by education, livestock holdings, family size, credit access, and training (P ≤ 10%), while the slope of farmland negatively affects the adoption of integrated methods. Most respondent farmers articulated that changes in the price of agricultural inputs (44.94%), lack of capital (19.1%), tenure security (16.1%), small livestock unit (14.61%), and labor intensiveness (5.24%) were the major challenges related to the adoption of these practices. Therefore, improving access to training, extension services, and credit, experience sharing, improving land productivity per unit area, and addressing the major challenges specific to each practice are crucial to promoting sustainable land management in the district.